A NOVEL SCHIFF BASE DERIVATIVE FOR EFFECTIVE TREATMENT OF AZOXYMETHANE INDUCED COLON CANCER - Dogan, Aysegul; Basak, Nese; Demirci, Selami; Telci, Dilek; Dede, Bulent; Tuzcu, Mehmet; Sahin, Fikrettin (Int Journal Pharmaceutical Sciences & Research, 2014)
The field of cancer research has been emerged in recent years for the development of specific drugs to cancer treatment. New agents with the ability to provide efficient treatment by reducing side effects has led to new opportunities for improving agents for cytotoxic therapies. While there are several drugs for colon cancer treatment, researchers are trying to evaluate new agents or combinations of existing ones which can be used efficiently. Schiff bases with a wide range of variety and biological properties including anticancer activity might be used for colon cancer treatment. In the current study, a novel schiff base derivative synthesized by our group was tested in vivo for colon cancer. In a model of azoxymethane (AOM) induced colorectal cancer, chemopreventive properties of schiff base was also analyzed in rats. While AOM induced de novo crypt formation, adenocarcinoma and dysplasia development, schiff base application reduced the number of aberrant crypt foci (ACF), dysplasia or adenocarcinoma. Analysis of the intestinal mucosa showed that peritoneal administration of SB complex not only decreased the protein expression of COX-2, Bcl-2 and NF-kappa B but also enhanced the Bax expression suggesting the apoptotic and anti-proliferative effects for this compound. Our findings showed that SB complex might be used for the colorectal cancer treatment. Further studies are highly warranted to obtain additional insights and identify mode of action for the schiff base.
Keywords: Schiff base; colon cancer; azoxymethane; aberrant crypt foci